2017
DOI: 10.1111/iej.12772
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk for cardiovascular mortality for patients with root filled teeth in a Finnish population

Abstract: Having ≥1 root filled teeth was associated with significantly lower odds for prevalent CAD cross sectionally and lower risk of cardiovascular mortality prospectively. These reduced associations with CVD were independent of periodontitis or serum CRP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
(106 reference statements)
2
15
0
1
Order By: Relevance
“…The prevalence of RFT was not associated with cardiovascular events. This result is in accordance with previous findings [ 58 ], although other studies have found an association between endodontic status and the risk of cardiovascular event, both in the sense of increasing it [ 21 , 60 ] or decreasing it [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of RFT was not associated with cardiovascular events. This result is in accordance with previous findings [ 58 ], although other studies have found an association between endodontic status and the risk of cardiovascular event, both in the sense of increasing it [ 21 , 60 ] or decreasing it [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, treatment of AP through root canal treatment (RCT) has been shown to improve systemic inflammation, ameliorating early endothelial dysfunction [ 29 ]. In addition, it has been reported that having RFT is associated with a lower probability of suffering coronary heart disease and a lower risk of mortality from cardiovascular events [ 30 ]. Despite all these findings, the causal association between oral infections and ACVD cannot be considered proven [ 10 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…2009), and others suggest even protective features of root canal fillings, noting that they might be subject to bias (Meurman et al . 2017, Cowan et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…= 1.04–3.02; p < 0.05) ( 20 ). However, it has been also shown that having ≥1 RFT is associated with significantly lower odds for prevalent coronary artery disease and lower risk of cardiovascular mortality ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Respect to RCT, the results are obviously inconsistent. Some studies find correlation between the prevalence of RCT and CVDs ( 18 , 19 ), but other find no association ( 43 ), or even other find that RCT is a protective factor against CVDs ( 21 ).…”
Section: Discussionmentioning
confidence: 99%